Investigation on Potential of Recycle Plastic Bottles as a Crash Cushion for Road Barrier - Ambak, Kamarudin; Hadipramana, Josef; Abas, Nurul Aimi; Mohkatar, Shahrul Niza; Jani, Zainorizuan (International Journal of Integrated Engineering, 2018)
Road accident is a major problem in the country and should be dealt with an effective ways. Road furniture is one of the factors that contributing an accidents than other factors. Therefore, this study focuses on waste material such as recycle plastic bottle that potential to be used as a road barrier and crash cushion. The objective of this study are to investigate the potential of plastic bottles filled with sand as crash cushion, examine the impact strength of plastic bottles and designing crash cushion by using recycled materials. Some plastic bottles of soft drinks containing ordinary sand was prepared and undergone experimental and simulation works. Free fall Impact test that imposed on the plastic bottles has been carried out to identify the strength and its energy absorption. The numerical simulation of impact test was conducted using Finite Element Method to obtain impact failure and to observe its details response under low velocity impact loads. The numerical results by employing FEM well agreed with practical works. Where, the absorption of energy from the impact test shows that the difference does not exceed 50%. In addition, the deformation of both test are almost similar. Therefore, the use of recycled materials such as plastic bottles filled with sand as crash cushions that can be considered as alternative and environmentally friendly materials.